2014
DOI: 10.1007/s11119-014-9367-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brown planthopper infestation based on SPAD and spectral data from rice under different rates of nitrogen fertilizer

Abstract: Reflectance and SPAD readings were measured in rice grown under different nitrogen fertilizer rates and infested with different numbers of brown planthopper (BPH), Nilaparvata lugens, to assess the relationships among these variables. The results showed that SPAD readings and reflectance from rice were significantly affected by BPH infestations and nitrogen fertilizer rates, whereas there was no interaction between the two factors. SPAD readings and reflectance decreased as BPH infestations increased but they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
2
15
0
2
Order By: Relevance
“…The SPAD value and photosynthetically active radiation (PAR) are key determinants for plant growth and development. The SPAD value represents chlorophyll content in rice leaves and indirectly reflects the photosynthetic capacity of plants [25][26][27]. Numerous studies have reported that the accumulated biomass of plants is closely related to the amount of photosynthetically active radiation intercepted by the canopy [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…The SPAD value and photosynthetically active radiation (PAR) are key determinants for plant growth and development. The SPAD value represents chlorophyll content in rice leaves and indirectly reflects the photosynthetic capacity of plants [25][26][27]. Numerous studies have reported that the accumulated biomass of plants is closely related to the amount of photosynthetically active radiation intercepted by the canopy [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, SPAD values of flag leaf are one index closely related with N content of leaf. Many reports found photosynthesis and grain yield could be affected by the SPAD value of flag leaf at grain filling stage (Ramesh et al, 2002;Jiang et al, 2012;Huang et , and it was reported that the reasonable SPAD value could improve yield, but it varied in different rice varieties. In this study, the SPAD value of flag leaf was about 27-34 at grain filling stage in early rice, and 32-36 in late rice.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to detecting BPH infestation is based on SPAD (Special Products Analysis Division) reading and reflectance of the rice. The results in [9,21] show that SPAD reading and reflectance from rice are significantly effected by BPH infestation. The spectral reflectance from rice canopy significantly decreased in the near-infrared wavelength range as BPH infestations increased.…”
Section: Related Workmentioning
confidence: 97%